In Vitro Bactericidal Activity of Bacopa Monnieri Leaf Extracts on Human Pathogenic Bacteria - Sape, Subba Tata (Sciences of Phytochemistry, 2025)
The increasing resistance of bacteria to conventional antibiotics poses a global health challenge, emphasizing the urgent need to discover new antibacterial compounds to combat hard-to-treat infections. This study aims to evaluate the bactericidal activity of crude leaf extracts from the multi-medicinal plant Bacopa monnieri against six bacterial strains. The crude extracts, prepared at different concentrations (100, 200, and 300 µg/mL), were tested for efficacy using the agar well diffusion method. Among the tested extracts, the ethanol extract exhibited the highest bactericidal activity, followed by chloroform and hexane extracts. Notably, all three solvent extracts at 300 µg/mL were most effective against Staphylococcus aureus, with inhibition zones of 21.5 mm (ethanol), 16.12 mm (chloroform), and 10.3 mm (hexane). In contrast, the lowest antibacterial activity was observed against Proteus vulgaris, with inhibition zones of 15.3 mm (ethanol), 10.2 mm (chloroform), and 5.6 mm (hexane). These findings suggest that the ethanol extract of B. monnieri is a promising candidate for the development of novel antibacterial compounds.